Electrostatic Regulation of TEMPO Oxidation by Distal Molecular Charges. Issue 16 (24th August 2020) - Zhang, Long; Ciampi, Simone; Gooding, J. Justin
Abstract: We define, experimentally, the effect of intramolecular electric fields, generated from the positive charge of ferricenium cations, over the oxidation potential of 2, 2, 6, 6 ‐ tetramethyl ‐ 1 ‐ piperdinyloxy (TEMPO). We synthesized a TEMPO derivative, where the nitroxide is linked to a ferrocene unit. We have used this molecule to study the influence on the electrostatic cross‐talk between positively charged ferriceniums and TEMPO units by solvent dielectric, level of electrolytic support, and Lewis acid/base character of electrolyte ions. The magnitude of thermodynamic anodic shift of the TEMPO oxidation, after the ferrocene unit is converted to a ferricenium cation, increases with decreasing dielectric constant of the solvent, electrolytic concentration, and Lewis basicity strength (i. e. between ferriceniums and electrolyte anions). This work demonstrates an approach to use electrostatic forces, here delivered by intramolecular charged cations, to tune the oxidation energy for nitroxides in ionic solutions. Abstract : On the up : The magnitude of thermodynamic anodic shift of the TEMPO oxidation in Fc‐TEMPO molecules, after the ferrocene unit is converted to a ferricenium cation, increases with decreasing dielectric constant of solvent, electrolytic concentrations, and Lewis acid/base strength.